2005
DOI: 10.1126/science.1122165
|View full text |Cite
|
Sign up to set email alerts
|

Radar Soundings of the Subsurface of Mars

Abstract: International audienceThe martian subsurface has been probed to kilometer depths by the Mars Advanced Radar for Subsurface and Ionospheric Sounding instrument aboard the Mars Express orbiter. Signals penetrate the polar layered deposits, probably imaging the base of the deposits. Data from the northern lowlands of Chryse Planitia have revealed a shallowly buried quasi-circular structure about 250 kilometers in diameter that is interpreted to be an impact basin. In addition, a planar reflector associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
239
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 337 publications
(252 citation statements)
references
References 16 publications
(12 reference statements)
10
239
0
Order By: Relevance
“…Indeed, they reveal only the ice/ rock interface in the North PLD's, i.e., the base of the polar cap [Picardi et al, 2005]. This aspect simplifies our model to three homogeneous layers (see Figure 1).…”
Section: Inversion Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, they reveal only the ice/ rock interface in the North PLD's, i.e., the base of the polar cap [Picardi et al, 2005]. This aspect simplifies our model to three homogeneous layers (see Figure 1).…”
Section: Inversion Techniquementioning
confidence: 99%
“…[3] Both the North [e.g., Picardi et al, 2005;Putzig et al, 2009] and the South [e.g., Plaut et al, 2007;Seu et al, 2007a] PLD's have been observed by the MARSIS [Picardi et al, 2004] and SHARAD [Seu et al, 2007b] subsurface sounding radars, which operate in the HF and VHF bandwidth, respectively. Subsurface radar sounding is the only viable technique that can provide information in the third dimension (depth) of a planet from orbit.…”
Section: Introductionmentioning
confidence: 99%
“…GPR is often employed for nondestructive testing close to a ground interface with the aim of localizing buried targets in the shallow subsurface, such as in landmine detection and other important civil, forensic, archaeological, geophysical, and planetary applications [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The physical conclusion related to (9) is that a linear reconstruction will be substantially the same for dielectric and magnetic targets (we have a formal difference of the two object functions, but it is irrelevant), and in particular, any linear reconstruction will not able to distinguish whether the focused target was dielectric or magnetic (or both) contrasted with the surrounding soil.…”
Section: Diffraction Tomography Relationshipsmentioning
confidence: 99%
“…Recently, it has been outlined that the anomalies and/or the background scenario can exhibit magnetic properties, even in the radio-frequency and microwave range [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%